Bruk av digitale ordbøker i norsk skule - Hovdenak, Marit; Ims, Ingunn Indrebø (Nordiske Studier i Leksikografi, 2018)
This article presents the material from an online survey in 2014 which reveals if, how and in what way teachers and their students in the Norwegian schools use and relate to monolingual online dictionaries in Norwegian. 487 teachers and 5172 students from all over Norway responded to the survey. The findings are interesting with respect to several of the objectives of The Language Council of Norway, among others the responsibility to promote the two Norwegian written standards Bokmål and Nynorsk in the classrooms and ensure that the dictionaries are up to date.